Stedman's Nachrichten von Surinam und von seiner expedition gegen die rebellischen neger in dieser kolonie in den Jahren 1772 bis 1777 : ein Auszug aus dem englischen original (1797)
"Narrative of a five years expedition, against the revolted Negroes of Surinam in Guiana on the wild Coast of South-America from the year 1772 to 1777 : elucidating the history of that Country and describing its productions, viz : Quadrupedes, Birds, Fishes, Reptiles, Trees, Shrubs, Fruits and Roots ; with an account of the Indians of Guiana and Negroes of Guinea"